Ideological Censorship in Lithuania in 1948–1955: Adjustment of the System - Streikus, Arūnas (Genocidas ir rezistencija, 2024)
Research conducted confirms that the crucial stage in the Sovietization of Lithuanian cultural life started at the end of fifth decade of the 20th century. The changed key points of public rhetoric, application of repressive measures, stricter control of book publishing and periodical press, more active actions of Glavlit (Chief Agency for Protection of Military and State Secrets) in cleaning the book funds showed the efforts of the authorities to implement as soon as possible a model of universal ideological control, characteristic of later Stalinism. The attack, gaining momentum against the Lithuanian cultural workers who were not able to adapt to the requirements of the new system, was instigated by the ideological campaigns arising one after another from Moscow.The Soviet mechanism of ideological censorship was finally formed at the beginning of the sixth decade when Glavlit was delegated with a task to take care of political control over art works, theatre and music repertoire. Due to the lack of the qualified staff, LSSR Glavlit failed not only to perform the new functions efficiently, but also to ensure the smooth censorship of the printed word. The lower link of ideological censorship, consisting of the leadership of the creative unions, the Board of Art Affairs and the editorial offices of publishing houses and periodical publications, operated still more unreliably, therefore in tackling political control tasks of public discourse, an important role belonged to the LCP CC. The active participation of the party machinery was also related with the fight that took place at the beginning of the sixth decade of the 20th century at the top of the local power between the representatives of the pro-Communist intellectuals of the senior generation, to whom the illusions of national Communism were not alien, and the apologists of Stalinist cultural policy. In the last years of J. Stalin’s rule the positions of the latter group strengthened, therefore the first impulses of cultural life liberalization reached Lithuania only in 1956.
Keywords: Soviet regime; censorship; communist ideology; culture